Debt adjustment and growth: some lessons from the Mexican experience - Trevino, Jose Angel Gurria (UWI MonaJA, 1994)
Focuses on how Mexico dealt with its external debt crisis. Looks at topics such as external debt restructuring; fiscal reform; stabilization policy and economic growth; deregulatory policy; the external sector; foreign investment; and, poverty alleviation.